Phase, microstructure and ferroelectric properties of new complex-structured ferroelectric ceramics in the PZT-SBN system - Orapim Namsar (2018)
This study aimed to fabricate and characterize new complex-structured ceramics with formula (1-x)Pb(Zr0.52Ti0.48)O3-xSrBi2Nb2O9or (1-x)PZT-xSBN (where x=0, 0.1, 0.3 and 0.5 weight fraction). The ceramics were prepared by a solid-state mixed-oxide method and sintered at temperatures between 1000 and 1250 °C. Optimum sintering temperature for this system was found to be 1050 °C for 3 h dwell time. X-ray diffraction patterns of (1-x)PZT-xSBN powders showed peak intensities of two-phase mixture corresponding to the relative amount of each phase as a result of SBN addition. Microstructure of (1-x)PZT-xSBN ceramics showed a variation in grain shape and grain size. The small addition of SBN (x=0.1) was also found to improve ferroelectric properties of pure PZT ceramic. © 2012 Elsevier Ltd and Techna Group S.r.l.